2018
DOI: 10.1021/acsami.8b03182
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Ion Implantation of Silk Biomaterials Enabling Direct Covalent Immobilization of Bioactive Agents for Enhanced Cellular Responses

Abstract: Silk fibroin isolated from Bombyx mori cocoons is a promising material for a range of biomedical applications, but it has no inherent cell-interactive domains, necessitating functionalization with bioactive molecules. Here we demonstrate significantly enhanced cell interactions with silk fibroin biomaterials in the absence of biofunctionalization following surface modification using plasma immersion ion implantation (PIII). Further, PIII treated silk fibroin biomaterials supported direct covalent immobilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 56 publications
1
65
0
Order By: Relevance
“…This may be due to the fact that when the nitrogen-containing functional groups were implanted on the surface of the materials aer plasma treatment, a suitable microenvironment was created which promoted cell adhesion and proliferation, C60N6 group of high relative potential was more suitable for the biological behavior of cells. Previous studies 17,34,40,41 have also shown that positively charged nitrogen functionalities could promote cell expression thus improving biological activity, which was consistent with our ndings.…”
Section: Discussionsupporting
confidence: 93%
“…This may be due to the fact that when the nitrogen-containing functional groups were implanted on the surface of the materials aer plasma treatment, a suitable microenvironment was created which promoted cell adhesion and proliferation, C60N6 group of high relative potential was more suitable for the biological behavior of cells. Previous studies 17,34,40,41 have also shown that positively charged nitrogen functionalities could promote cell expression thus improving biological activity, which was consistent with our ndings.…”
Section: Discussionsupporting
confidence: 93%
“…SF has reactive carboxyl and amino groups in its side chains that can be conjugated to different functional groups. For example, plasma immersion ion implantation (PIII) treatments have been used to covalently bind proteins to the SF surface and improve cellular interactions ( Kondyurin et al, 2018 ). Another simple surface modification technique involves plasma etching for grafting poly acrylic acid (pAAc) and poly hydroxyethylmethacrylate on regenerated SF films.…”
Section: Tailoring Silk Biomaterials To Control Cellular Fatementioning
confidence: 99%
“…[ 47–51 ] Over the last decade, we have used PIII for reagent‐free, covalent attachment of biomolecules, such as proteins, peptides, and DNA on surfaces. [ 12,52–56 ] The covalent attachment occurs when molecules in physical contact with the surface react with surface‐embedded radicals generated by the implanted ions. Such a chemical linker‐free, radial‐based mechanism for biomolecule immobilization makes it possible to tune the surface density and orientation of molecules by simply tuning the solution pH or applying external electric fields during the immobilization.…”
Section: Introductionmentioning
confidence: 99%